Factors Analysis With Reference to Training of Line Staff in Jaipur Dairy, Rajasthan - Banga, Shraddha (Prabandhan: Indian Journal of Management, 2009)
Due to highly competitive market and demanding consumers, producers require skilled and dedicated workforce. Especially, in milk industry which deals in one of the most perishable FMCG industry. The expansion of product line of milk products has increased the use of capital in milk plants which furthers the cause of proper training of labour force. It becomes imperative to examine the attitude of workers to understand the important factors for designing training programmes. The study identifies key forms of training using factor analysis and examines their managerial implications.